Multiphonon conduction in doped poly (p-phenylene) - Campos, M. (2001)
The de electrical conductivity of doped poly (p-phenylene) conducting polymer has been reported in the temperature range of 50-300 K. The experimental results have been analyzed in the framework of different hopping models. We have observed that the conductivity is non activated and that the Mott's and Efros-Shklovskii variable range hopping, and also the small polaron hopping cannot interpret the temperature dependence of the conductivity data over the entire temperature range of measurement. It has been observed that the charge transport process occurs by the multiphonon assisted hopping of the charge carriers that interact weakly with phonons.